Data-Driven Decision Making for Smart Agriculture - Abhishek Beriya; V.N. Saroja (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2019)
Agriculture is a very important sector of the Indian economy and it accounts for 49% of the employment and one-sixth of the GDP. Information and communication have always mattered in agriculture. Updated information allows farmers to benefit through better and informed decision making. It has been the endeavour of agencies concerned with agriculture to share such information to benefit farmers as well as a challenge for them to find effective ways of sharing. Right and timely information can help farmers in all aspects of the agricultural cycle from pre-sowing to post harvest. Information and Communication Technologies (ICTs) have emerged as a very strong tool to share the information with farmers effectively, efficiently and in a low cost ways. We have attempted to list the possibilities, challenges and few initiatives as examples in ICT for Agriculture in the 3 major domains of agriculture namely: ICT in Empowering farmers through better communication and knowledge sharing, ICT in Insurance, Finance, Remote Sensing, Weather Prediction etc., ICT in improving efficiency of the Agriculture Supply Chain, market access for farm inputs and post-harvest to benefit farmers. We have also reviewed the existing literature on this subject and there have been many discussions around developing decision support systems for farmers. However, a comprehensive decision support system to provide customized advisory and help an individual farmer to make choices, which crop to sow, when to sow, when to harvest (in the window available to harvest) and whether to instantly sell or go for storage, all with the objective of better price realization, in a smallholder farmer/ developing country context, is yet to emerge. It is this gap which we have identified and which we want to make efforts to address. (...)
Keywords: 330